Temperature and relativity - Costa, Sandro S. [UNESP]; Matsas, George E.A. [UNESP] (Elsevier, 1995)
We investigate whether inertial thermometers moving in a thermal bath behave as being hotter or colder. This question is directly related with the classical controversy concerning how temperature transforms under Lorentz transformations. Rather than basing our arguments on thermodynamical hypotheses, we use plain relativistic quantum field theoretical methods. © 1995.